2013
DOI: 10.1080/02757540.2013.810720
|View full text |Cite
|
Sign up to set email alerts
|

Effects of fertiliser and intercropping on cadmium uptake by maize

Abstract: This study investigated the effect of fertilisation and intercropping on the uptake of cadmium (Cd) by maize plants (Zea mays L. var. Guangtian-2). Maize was intercropped with soybean, peanut, chickpea, alfalfa, adzuki bean, garden pea, amaranth, Chinese mustard, and flowering Chinese cabbage. The results showed that most legumes substantially enhanced Cd uptake by maize under different fertiliser treatments. Cd accumulation in the leaf tissues of maize was increased by garden pea to 1.5 times the amount in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 35 publications
0
4
0
1
Order By: Relevance
“…When TF >1, it can be inferred that plants can transfer the heavy metal elements from roots to the aboveground part. When TF <1, plants prevent the transport of heavy metals from roots to the aboveground parts ( 59 ). As seen in Figure 6 , the TF of Pb in peanuts was high, in contrast, the TF of Cu and As was small, and hence the transfer ability was low.…”
Section: Resultsmentioning
confidence: 99%
“…When TF >1, it can be inferred that plants can transfer the heavy metal elements from roots to the aboveground part. When TF <1, plants prevent the transport of heavy metals from roots to the aboveground parts ( 59 ). As seen in Figure 6 , the TF of Pb in peanuts was high, in contrast, the TF of Cu and As was small, and hence the transfer ability was low.…”
Section: Resultsmentioning
confidence: 99%
“…The contaminations of Pb and Cd in the feeds could be due to the use of contaminated feed ingredients in the production of the feeds. Also, the presence of cadmium in the feeds cannot be excluded from the use of phosphate fertilizers in agricultural production of maize [34].…”
Section: Discussionmentioning
confidence: 99%
“…A new approach, intercropping/co-cropping system was introduced to phytoremediation of pollutants in contaminated soils, while also growing an agricultural crop. Li et al [49] studied the effects of intercropping 7 crops (Brown Bean, lentil, chickpea, alfalfa, rape, Amaranthus hypochondriacus L. and Mexico corn grass) on the Cd uptake by maize. The results showed that only lentil reduced the maize biomass, 4 leguminous crops increased Cd accumulation of maize, and Brown Bean and chickpea worked most efficiently, which increased Cd quantity of 1.6 times and 2.1 times in maize.…”
Section: Energy and Environment Materialsmentioning
confidence: 99%